Climate change and plant regeneration from seed - Walck, J.; Hidayati, S.; Dixon, Kingsley; Thompson, K.; Poschlod, P. (2011)
At the core of plant regeneration, temperature and water supply are critical drivers for seed dormancy (initiation, break) and germination. Hence, global climate change is altering these environmental cues and will preclude, delay, or enhance regeneration from seeds, as already documented in some cases. Along with compromised seedling emergence and vigour, shifts in germination phenology will influence population dynamics, and thus, species composition and diversity of communities. Altered seed maturation (including consequences for dispersal) and seed mass will have ramifications on life history traits of plants. Predicted changes in temperature and precipitation, and thus in soil moisture, will affect many components of seed persistence in soil, e.g. seed longevity, dormancy release and germination, and soil pathogen activity. More/less equitable climate will alter geographic distribution for species, but restricted migratory capacity in some will greatly limit their response. Seed traits for weedy species could evolve relatively quickly to keep pace with climate change enhancing their negative environmental and economic impact. Thus, increased research in understudied ecosystems, on key issues related to seed ecology, and on evolution of seed traits in nonweedy species is needed to more fully comprehend and plan for plant responses to global warming.